Prove that Fib(n) is the closest integer to ϕn/√5, where ϕ = (1 + √5)/2. Hint: Let ψ = (1 - √5)/2. Use induction and the definition of the Fibonacci numbers (see section 1.2.2) to prove that Fib(n) = (ϕn - ψn)/√5.
The definition of Fib(n) given in section 1.2.2 is:
Fib(n) = | 0 | if n = 0 |
1 | if n = 1 | |
Fib(n - 1) + Fib(n - 2) | otherwise |
First, let's prove the base cases of n = 0 and n = 1. When n = 0:
(ϕ0 - ψ0)/√5 = (1 - 1)/√5 = 0/√5 = 0 = Fib(0)and when n = 1:
(ϕ1 - ψ1)/√5 = (((1 + √5)/2)1 - ((1 - √5)/2)1)/√5 = ((1 + √5)/2 - (1 - √5)/2)/√5 = ((1 + √5 - 1 + √5)/2)/√5 = 2√5/2/√5 = √5/√5 = 1 = Fib(1)To then prove by induction that their hint holds for all n we then first make the assumptions that the following two formulae hold:
Fib(n - 1) = (ϕn-1 - ψn-1)/√5 Fib(n) = (ϕn - ψn)/√5Next we try to prove that, given these assumptions, the formula also holds for n + 1. I.e. we need to prove that Fib(n + 1) = (ϕn+1 - ψn+1)/√5. Before we do this, a little side track... We already know that ϕ2 = ϕ + 1. We can also prove the corresponding equation of ψ2 = ψ + 1:
ψ2 = ((1 - √5)/2)2 = (1 - √5)/2)(1 - √5)/2) = (1 - √5)(1 - √5)/4 = (1 - 2√5 + 5)/4 = (6 - 2√5)/4 = (3 - √5)/2 = (1 - √5)/2 + 1 = ψ + 1Okay, having done that, back to our proof for n + 1:
Fib(n + 1) = Fib(n) + Fib(n - 1) = (ϕn - ψn)/√5 + (ϕn-1 - ψn-1)/√5 = (ϕn - ψn + ϕn-1 - ψn-1)/√5 = ((ϕn + ϕn-1) - (ψn + ψn-1))/√5 = ((ϕ + 1)ϕn-1 - (ψ + 1)ψn-1)/√5 = (ϕ2ϕn-1 - ψ2ψn-1)/√5 = (ϕn+1 - ψn+1)/√5
So we've proved by induction that Fib(n) = (ϕn - ψn)/√5. But why does that prove that Fib(n) is the closest integer to ϕn/√5?
Well if Fib(n) is the closest integer to ϕn/√5 then ϕn/√5 must be within 1/2 of Fib(n). In other words, we need to prove that:
|(Fib(n) - ϕn/√5)| ≤ 1/2Recall that we've already shown that Fib(n) = (ϕn - ψn)/√5, so we can proceed as follows:
|(Fib(n) - ϕn/√5)| ≤ 1/2 ⇒ |((ϕn - ψn)/√5 - ϕn/√5)| ≤ 1/2 ⇒ |(-ψn/√5)| ≤ 1/2 ⇒ |ψn/√5| ≤ 1/2 ⇒ |ψn| ≤ √5/2So we just need to to prove that |ψn| ≤ √5/2:
- We know that, for any value of x such that -1 ≤ x ≤ 1 and any value of n ≥ 1, it's the case that 0 ≤ |(xn)| ≤ 1
- ψ = (1 - √5)/2 ≈ -0.6180, so 0 ≤ |ψn| ≤ 1
- √5/2 ≈ 1.1180
I did not understand why this
ReplyDelete= ((ϕn + ϕn-1) - (ψn + ψn-1))/√5
lead to this
= ((ϕ + 1)ϕn-1 - (ψ + 1)ψn-1)/√5
in case ϕ2=ϕ+1
For both ψ and ϕ, it is just a factorization
Delete(ϕ + 1)ϕ^n-1
= (ϕ^1*ϕ^(n-1) + ϕ^(n-1))
= (ϕ^(1 + n-1) + ϕ^n-1)
= (ϕ^n + ϕ^n-1)